Emerging Roles of Extracellular Vesicle-Delivered Circular RNAs in Atherosclerosis - Wen, Cheng; Li, Bowei; Nie, Lei; Mao, Ling; Xia, Yuanpeng (Frontiers in Cell and Developmental Biology, 2022)
Atherosclerosis (AS) is universally defined as chronic vascular inflammation induced by dyslipidaemia, obesity, hypertension, diabetes and other risk factors. Extracellular vesicles as information transmitters regulate intracellular interactions and their important cargo circular RNAs are involved in the pathological process of AS. In this review, we summarize the current data to elucidate the emerging roles of extracellular vesicle-derived circular RNAs (EV-circRNAs) in AS and the mechanism by which EV-circRNAs affect the development of AS. Additionally, we discuss their vital role in the progression from risk factors to AS and highlight their great potential for use as diagnostic biomarkers of and novel therapeutic strategies for AS.